The Effect of Three Instructional Elements on Achievement in Computer-Based Mathematics Instruction of Senior Secondary School Students in Nigeria - Omoniyi, Tayo; Gbenga, Gisanrin (Journal of Education in Black Sea Region, 2018)
This study investigated the effect of three instructional elements on achievement in computer-based mathematics instruction. The subjects were senior secondary school students who used four versions of computer-based instruction developed on compact disc to learn about the volume of solid shapes. The four versions of the programme were (1) a full version that had the three instructional elements (2) a version without objectives (3) a version without practice (4) a version without examples. The results indicated that the full package, which included objectives, practice and examples, had a significant effect on students’ achievement in the computer-based mathematics instruction. Furthermore, of the three elements, practice, had the most effect on the learners’ achievement. Implications of the findings on development of computer-based instructions are also discussed.